Postcard for Gaza / Jamizan Jalaluddin @ Mohd Rashid ... [et al.] - Jalaluddin @ Mohd Rashid, Jamizan; Abdul Wahab, Nurulakma; Abu Sujak, Farhanah (Faculty of Art and Design, 2021)
Inspiration from story of a mujahid, the only one people of Malaysia who fought for the land of Gaza, especially Gaza children. Nadir Al-Nuri, [29.06.21 08:52] Malam Cinta Palestin ‘If you are still impressed with what the Palestinian people are going through, prove that our silence on social media does not mean the disappearance of our spirit to support them. For me, Gaza is not a place of pilgrimage, not a place to come and go when you want, not to be left as you like. Gaza is my flesh and blood. Before I married with Gaza people in 2016, 300 orphans who were under CGM in 2013 called me Baba. I visited them house to house, celebrate their birthdays, make surprises with visit at school, wipe their heads until they are taller than me. After 10 years, Gaza has become my second country. The children of Gaza are my children. The young men of Gaza are my brothers and sisters’. This graphic work as a greeting is a sign of support for the efforts of Malaysia's people Nadir Al Nuri, Reem Al Menawi, wife and symbol of the great Palestinian woman and the wise little Naura, who remained and fought directly in Gaza for peace and solidarity. through the Cinta Gaza Malaysia Organization together with Tabung Anak Yatim Campaign and agencies and NGOs from Southeast Asia, especially Malaysia. Taking in the memories of the sacrifices of the children of heaven like Adik Rainaf Al Masri who has been a victim of Jewish greed.Also admire the spirit of the 'young journalist' to Nadine's tenacity in housing, schools and mosques in the brutal Israeli bombing. in the rain of bombs. the young Muhammad Nassar who believed in his dream to succeed in helping his family and the economy of his community even though his homes and family belongings were destroyed in the bombing.